2005
DOI: 10.1136/jmg.2005.040162
|View full text |Cite
|
Sign up to set email alerts
|

High throughput SNP and expression analyses of candidate genes for non-syndromic oral clefts

Abstract: Background: Recent work suggests that multiple genes and several environmental risk factors influence risk for non-syndromic oral clefts, one of the most common birth defects in humans. Advances in highthroughput genotyping technology now make it possible to test multiple markers in many candidate genes simultaneously. Methods: We present findings from family based association tests of single nucleotide polymorphism (SNP) markers in 64 candidate genes genotyped using the BeadArray approach in 58 case-parent tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 36 publications
1
51
0
Order By: Relevance
“…Cleft palate has various known and suspected genetic etiologies in humans [Stanier and Moore, 2004;Park et al, 2006]. One possibly causative gene is SATB2, encoding a cell type-specific transcription factor that functions as a regulator of the transcription of large chromatin domains.…”
Section: Introductionmentioning
confidence: 99%
“…Cleft palate has various known and suspected genetic etiologies in humans [Stanier and Moore, 2004;Park et al, 2006]. One possibly causative gene is SATB2, encoding a cell type-specific transcription factor that functions as a regulator of the transcription of large chromatin domains.…”
Section: Introductionmentioning
confidence: 99%
“…5,10,11 Previous studies showed that complete functional loss of Satb2 leads to increased apoptosis in the developing jaw primordia and subsequent down-regulation of the expression of genes (Pax9, Alx4 and Msx1) involved in craniofacial development in humans and mice. 12,13 Although initial cytogenetic studies showed two translocation break breakpoints on 2q32, which harbours SATB2 gene, 2 a meta-analysis of genome scans of cleft lip and palate indicated 2q32-q35 region as a clefting susceptibility locus. 14 Sequencing of 184 cleft lip and palate cases revealed T190A mutation in a single Philippine case, which was not found in CEPH controls.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, rs1939012:T-rs1783901:A haplotype was suggestive of a protective value against the condition (Table 6). MMP8 rs1939012 was recently found to be associated with genetic generalized epilepsy on a genomewide level [International League against Epilepsy Consortium on Complex Epilepsies, 2014], while rs1783901 in SCN3B was also implicated in association with nonsyndromic oral clefts [Park et al, 2006]. Considering that the lack of association of these SNPs individually could be due the small number of individuals in our study, we compared the SNP minor allele frequencies of patients in the Polish groups to the Eu-ropean population included in the gnomAD and 1000 Genomes Project databases; likewise, no significant differences were found (p = 0.5421 and p = 0.5317 for rs1939012; p = 0.8883 and p = 0.4396 for rs1783901, respectively).…”
Section: Discussionmentioning
confidence: 99%